The E3 ubiquitin-protein ligase Nedd4-2 regulates the sodium chloride cotransporter NCC but is not required for a potassium-induced reduction of NCC expression - Rosenbaek, Lena L.; Petrillo, Federica; van Bemmelen, Miguel X.; Staub, Olivier; Murali, Sathish K.; Fenton, Robert A. (Frontiers in Physiology, 2022)
Na+ and K+ balance is influenced by the activity of the sodium chloride cotransporter NCC in the distal convoluted tubule. NCC activity and abundance are reduced by high extracellular K+. The E3 ubiquitin ligase neural precursor cell expressed developmentally downregulated 4-2 (Nedd4-2) has been proposed as a modulator of NCC abundance. Here, we examined the functional role of Nedd4-2 on NCC regulation and whether Nedd4-2 is important for the effects of high extracellular K+ on NCC. Total and plasma membrane levels of ubiquitylated NCC were lower in NCC-expressing MDCKI cells after Nedd4-2 deletion. NCC and phosphorylated NCC (pT58-NCC) levels were higher after Nedd4-2 deletion, and NCC levels on the plasma membrane were elevated. No significant changes were seen after Nedd4-2 knockdown in the levels of SPAK and phosphorylated SPAK (pS373-SPAK), the major NCC regulatory kinase. Nedd4-2 deficiency had no effect on the internalization rate of NCC from the plasma membrane, but NCC protein half-life was increased. In ex vivo experiments with kidney tubule suspensions from Nedd4-2 knockout (KO) mice, high K+ reduced total and pT58-NCC regardless of genotype. We conclude that Nedd4-2 is involved in ubiquitylation of NCC and modulating its plasma membrane levels and degradation. However, Nedd4-2 does not appear to be important for K+ induced reductions in NCC abundance.